The Diversity of Several Flower Color Types of the Zinnia Plant (Zinnia elegans Jacq.) - Jantje Pongoh; Frangky Jessy Paat; Ronny Soputan (Jurnal Agroekoteknologi Terapan, 2022)
This study aims to determine the diversity of several traits of zinnia plants derived from four flower colors (red, white, yellow and purple). The activity was carried out from October 2020 to January 2021 in Pineleng Satu Village, Pineleng District, Minahasa Regency. For this purpose, each of the five plants was observed in a survey for plant height (cm), number of branches, number of flowers and diameter of flowers. Data were analyzed by means and analysis of variance. The results showed that the four types of color did not show any differences in the properties measured quantitatively.